2023
DOI: 10.30880/jtet.2023.15.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Non-School-Based Technical and Vocational Training for Disadvantaged Youths in South Africa

Abstract: Disadvantaged young people in Sub-Saharan Africa are the most stricken by unemployment because of their socio-economic background. Technical and vocational training programmes appear to be a remedy for their situation because the approaches of training delivery are practice-oriented. Using experiential learning theory, the article examines the enabling factors for the effectiveness of non-school-based technical and vocational training on skills acquisition. To get a full picture of the enabling fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Teacher professional development has garnered significant attention in the literature, both globally and within Africa. Numerous studies have investigated why teachers successfully develop classroom practices through professional development programs (Andersson & Palm, 2018;Nhlumayo, 2022;Mayombe, 2023). Additionally, the impact of professional development on teachers' understanding of specific topics, such as the nature of science (Chanetsa, 2023) and behavior management (Paramita et al, 2023), has been explored.…”
Section: The Concept Of Teacher Professional Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Teacher professional development has garnered significant attention in the literature, both globally and within Africa. Numerous studies have investigated why teachers successfully develop classroom practices through professional development programs (Andersson & Palm, 2018;Nhlumayo, 2022;Mayombe, 2023). Additionally, the impact of professional development on teachers' understanding of specific topics, such as the nature of science (Chanetsa, 2023) and behavior management (Paramita et al, 2023), has been explored.…”
Section: The Concept Of Teacher Professional Developmentmentioning
confidence: 99%
“…The effectiveness of professional development programs in African contexts has been a topic of interest (Mayombe, 2023). Some studies have identified challenges in implementing these programs, such as limited implementation of new practices by teachers (Andersson & Palm, 2018;Pohan et al, 2022).…”
Section: The Effectiveness Of Professional Development Programsmentioning
confidence: 99%
See 3 more Smart Citations